(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this research is to introduce Indonesia more deeply through the development of Nasyid Extracurricular activities at the Vuttisatvittayanusorn school. Vocal work is one of the things that is favored by students, especially women in the arts. Indonesia’s existence is well known in this country which is nicknamed the white elephant. Departing from this background, the author tries to develop Indonesian-language nasyid directly. This type of research is field research using a qualitative descriptive approach. The implementation of this activity went through several stages, namely: (1) Holding FGDs with Vuttisatvittayanusorn school teachers and making official art extracurriculars through collaboration. (2) Conduct open recruitment for Vuttisatvittayanusornschool students. (3) Preparing and designing training concepts and schedules (4) Presenting students at the implementation of the Islamic religious festival which is held every month in Krabi Thailand. The impact of implementing these activities is that students are able to develop vocal exercises through extracurriculars and increase interest and use Indonesian properly.